Legality - Theory and Practice - Thai, Pham Hong (VNU Journal of Science: Legal Studies; Vol 40 No 3DO - 10.25073/2588-1167/vnuls.4601, 2024)
Legality is a multifaceted, complex legal phenomenon. This phenomenon is central to legal theory and can be considered from many different aspects: political - ideological, economic - social, ethical, and legal. Law is the method of organizing and exercising state power, the principles of organization and operation of agencies, organizations, officials, civil servants, and the behavior of individuals. Today, under the impact of the market economy, misconducts, corruption, and legal violations tend to increase, so it is necessary to apply synchronous solutions to strengthen the legality